Model construction and performance analysis for asymmetric compound parabolic concentrator with circular absorber. (15th March 2023) - Zhang, Xueyan; Jiang, Shuoxun; Lin, Ziming; Gui, Qinghua; Chen, Fei
Abstract: Solar CPC (Compound Parabolic Concentrator, CPC) has advantages of static concentration, easy construction and wide application. In this paper, the A-CPC (Asymmetric Compound Parabolic Concentrator, A-CPC) with circular absorber operating at horizontal condition was studied. Based on the edge ray principle, the mathematical model of A-CPC with circular absorber was theoretically constructed, and the concentration performance was verified by the visual experiment. The study found that the average optical efficiency of A-CPC is 42.69% within the whole incidence angle, which is 9.2% higher than the S-CPC (Standard CPC, S-CPC) with the same specification. The results also showed that the maximum acceptable angle and the annual average daily direct radiation collection time of A-CPC reached 69° and 10.82 h, indicating the A-CPC has stronger adaptability to weather conditions. The total annual radiation collection amount of A-CPC, which is 3670 MJ/m 2, has surpassed that of S-CPC with 2880 MJ/m 2 by 27.4%. Economic analysis reveals that A-CPC can effectively save the total cost and has more friendly potential in application to engineering. Highlights: An A-CPC (Asymmetrical Compound Parabolic Concentrator, A-CPC) with circular absorber is constructed. A-CPC has a better optical efficiency curve. A-CPC enlarges its acceptance angle which can match seasonal heat demands. The beam radiation collection time of A-CPC is longer throughout the all year. The economy of A-CPC is significantly better than S-CPC(Standard CPC, S-CPC).